Joseph had a little overcoat - Taback, Simms (New York : Viking, 1999)
A very old overcoat is recycled numerous times into a variety of garments.
Caldecott Medal/Honor
School Library Journal starred
Publisher's Weekly
2.0
K-3
Keywords: Toy and movable books -- Specimens; Coats -- Fiction; Clothing and dress -- Fiction; Toy and movable books; Coats -- Fiction; Clothing and dress -- Fiction; Toy and movable books